Condensation of Rubisco into a proto-pyrenoid in higher plant chloroplasts - Nicky Atkinson; Yuwei Mao; Kher Xing Chan; Alistair J. McCormick (Nature Communications, 2020)
Introducing the pyrenoid-based CO2-concentrating mechanism of green algae into crops could greatly improve photosynthesis. Here, the authors show that expression of the algal linker protein EPYC1 and a plant-algal hybrid Rubisco in Arabidopsis chloroplasts leads to formation of a phase separated algal-like proto-pyrenoid.